Misuse, perceived risk, and safety issues of household insecticides: Qualitative findings from focus groups in Arequipa, Peru. - Anika J Larson; Valerie A Paz-Soldán; Claudia Arevalo-Nieto; Joanna Brown; Carlos Condori-Pino; Michael Z Levy; Ricardo Castillo-Neyra (Public Library of Science (PLoS), 2021)
Background The current body of research on insecticide use in Peru deals primarily with application of insecticides offered through Ministry of Health-led campaigns against vector-borne disease. However, there is a gap in the literature regarding the individual use, choice and perceptions of insecticides which may influence uptake of public health-based vector control initiatives and contribute to the thousands of deaths annually from acute pesticide poisoning in Peru. Methods Residents (n = 49) of the Alto Selva Alegre and CC districts of peri-urban Arequipa participated in seven focus group discussions (FGD). Using a FGD guide, two facilitators led the discussion and conducted a role-playing activity. this activity, participants insecticides (represented by printed photos of insecticides available locally) and pretended to "sell" the insecticides to other participants, including describing their qualities as though they were advertising the insecticide. The exercise was designed to elicit perceptions of currently available insecticides. The focus groups also included questions about participants' preferences, use and experiences related to insecticides outside the context of this activity. Focus group content was transcribed, and qualitative data were analyzed with Atlas.ti and coded using an inductive process to generate major themes related to use and choice of insecticides, and perceived risks associated with insecticide use. Results The perceived risks associated with insecticides included both short- and long-term health impacts, and safety for children emerged as a priority. However, in some cases insecticides were reportedly applied in high-risk ways including application of insecticides directly to children and bedding. Some participants attempted to reduce the risk of insecticide use with informal, potentially ineffective personal protective equipment and by timing application when household members were away. Valued insecticide characteristics, such as strength and effectiveness, were often associated with negative characteristics such as odor and health impacts. "Agropecuarios" (agricultural supply stores) were considered a trusted source of information about insecticides and their health risks. Conclusions It is crucial to characterize misuse and perceptions of health impacts and risks of insecticides at the local level, as well as to find common themes and patterns across populations to inform national and regional programs to prevent acute insecticide poisoning and increase community participation in insecticide-based vector control campaigns. We detected risky practices and beliefs about personal protective equipment, risk indicators, and safety levels that could inform such preventive campaigns, as well as trusted information sources such as agricultural stores for partnerships in disseminating information.